Active Fan Era In Terms Of Culture Industry: Social Media's Effect on Football Club-Fan Relationships - (:unkn) unknown (INT ORGANIZATION CENTER ACAD RESEARCH, 2014)
The relations between football clubs and their fans have been in the center of the arguments nowadays. As new communication technologies, especially social media arose, it effected the relations between fans and football clubs as it also effected many other sectors. As fans became more active, football clubs have increased their interest towards their followers. When funds started getting into the football world, it started making football itself and its fans industrialized. Since then football clubs started to be interested in having professional corporate communication by using social media. This paper aims to review the role of social media in the relations between fans and football clubs, football as an industrial object and how do football teams use the new communication channels. To reach this goal, this paper tried to observe the changes in the Twitter, Facebook and YouTube accounts of the teams that won the trophies in Liga BBVA and Spor Toto Super League.
Keywords: Culture Industry; Social Media; Football Industry